2018
DOI: 10.3390/ijms19113562
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Provides Insights into the Markers of Resting and LPS-Activated Macrophages in Grass Carp (Ctenopharyngodon idella)

Abstract: Macrophages are very versatile immune cells, with the characteristics of a proinflammatory phenotype in response to pathogen-associated molecular patterns. However, the specific activation marker genes of macrophages have not been systematically investigated in teleosts. In this work, leukocytes (WBC) were isolated using the Percoll gradient method. Macrophages were enriched by the adherent culture of WBC, then stimulated with lipopolysaccharide (LPS). Macrophages were identified by morphological features, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…We have also found that the expression of eight macrophage-related genes ( h2-eb1 , cd74 , cd68 , marco , capg , mpeg1 , cd200r1 , and csf1r ) was highest in AIC among selected cell type linked genes ( Figure 9 ) although the expression in AKC was significantly higher than those of AIC ( Figure 5 ). Our results are in agreement with another HK transcriptomic study; carp HK macrophage-like cells had higher expression of cd68 and mcsfr compared to those of HK leukocytes ( Hu et al, 2018 ). Furthermore, a study conducted by Jenberie et al (2018) revealed the higher expressions of csf1r and marco in HK macrophage-like cells.…”
Section: Discussionsupporting
confidence: 93%
“…We have also found that the expression of eight macrophage-related genes ( h2-eb1 , cd74 , cd68 , marco , capg , mpeg1 , cd200r1 , and csf1r ) was highest in AIC among selected cell type linked genes ( Figure 9 ) although the expression in AKC was significantly higher than those of AIC ( Figure 5 ). Our results are in agreement with another HK transcriptomic study; carp HK macrophage-like cells had higher expression of cd68 and mcsfr compared to those of HK leukocytes ( Hu et al, 2018 ). Furthermore, a study conducted by Jenberie et al (2018) revealed the higher expressions of csf1r and marco in HK macrophage-like cells.…”
Section: Discussionsupporting
confidence: 93%
“…We likewise noticed a 16-fold upregulation in carp M1 macrophages. The chemokine ccl20a was also mentioned as increased in LPS-stimulated macrophages in grass carp 23 in the same study and was also substantially (8 log2 fold) increased as one ccl20a paralog in carp M1 macrophages, although not among the most highly expressed genes. Chemokine receptors cxcr3 were mentioned as markers of M1 (cxcr3.1) and M2 (cxcr3.2) macrophages of grass carp, ayu and spotted green pufferfish 22 .…”
Section: Discussionmentioning
confidence: 61%
“…In vivo, macrophage polarization has been studied using tnfα / mpeg1 20 double transgenic zebrafish and preliminary findings show differences in expression of pro- and anti-inflammatory markers in tnfα + and tnfα - macrophages. In addition, some work towards a full transcriptional phenotype has been undertaken in tnfα / mpeg1 double transgenic zebrafish 21 and other teleosts 22 , 23 . Taken together, these studies provide the foundation to understand macrophage polarization in fish.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 72.47 Gb of clean data including 483.14 million read were generated from the three libraries (control group (CG), experiment group 4 h (EG4h), experiment group 18h (EG18h)). Next, we used Hisat 2 (v2.0.1) software to map clean reads to the grass carp genome [29] references and their average mapping coverage percentages in the three libraries were 93.38% (CG), 93.50% (EG4h), and 92.66% (EG18h). The detailed data (Table 1) suggested good coverage of the assembled transcripts by the sequencing read.…”
Section: Resultsmentioning
confidence: 99%